2018
DOI: 10.1111/1346-8138.14217
|View full text |Cite
|
Sign up to set email alerts
|

Primary scarring alopecia: A retrospective study of 89 patients in Taiwan

Abstract: Primary scarring alopecia (PSA) is caused by irreversible damage to the hair epithelial stem cells that reside in hair follicles. There is limited published work regarding PSA amongst the Asian population. The aim of this study was to evaluate the clinical features and to characterize the subtypes of PSA in southern Taiwan. In this retrospective case series, we reviewed 89 patients with pathology-confirmed PSA. The data was collected from National Cheng Kung University Hospital between 1988 through 2016. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
29
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 16 publications
10
29
3
2
Order By: Relevance
“…Folliculitis decalvans is a pustular scarring alopecia with distinct features of progressive permanent destruction of follicles with scarring and the emergence of grouped tufted hairs. Folliculitis decalvans is localised almost exclusively to the scalp and only rarely reported on the limbs . Our case was defined both by the clinical and histological features and the response to prolonged antibiotic courses combined with topical corticosteroids.…”
Section: Discussionmentioning
confidence: 95%
“…Folliculitis decalvans is a pustular scarring alopecia with distinct features of progressive permanent destruction of follicles with scarring and the emergence of grouped tufted hairs. Folliculitis decalvans is localised almost exclusively to the scalp and only rarely reported on the limbs . Our case was defined both by the clinical and histological features and the response to prolonged antibiotic courses combined with topical corticosteroids.…”
Section: Discussionmentioning
confidence: 95%
“…Lymphocytic PSA has a female predominance, and neutrophilic PSA mainly affects males with younger age of onset. 64 By contrast, a study from China reported a ratio of lymphocytic to neutrophilic PSA of 1:1.3. Neutrophilic PSA also occurs more in men, but mostly in their middle age.…”
Section: Non-scarring Alopecias In Asiansmentioning
confidence: 92%
“…A recent series of scarring alopecia in adult Asian females demonstrated an incidence of 12.4%, suggesting Asian teenage girls may also be at increased risk for the disease. 27 Autosomal dominant inheritance 28 has been proven by identification of a pathogenic variant in PADI3 a gene involved in hair shaft formation, in some Black women with CCCA. 29 Partial penetrance occurs in familial cases.…”
Section: Central Centrifugal Cicatricial Alopecia (Ccca)mentioning
confidence: 99%